Blast wave parameters at diminished ambient pressure. (April 2015) - Silnikov, M.V.; Chernyshov, M.V.; Mikhaylin, A.I.
Abstract: Relation between blast wave parameters resulted from a condensed high explosive (HE) charge detonation and a surrounding gas (air) pressure has been studied. Blast wave pressure and impulse differences at compression and rarefaction phases, which traditionally determine damage explosive effect, has been analyzed. An initial pressure effect on a post-explosion quasi-static component of the blast load has been investigated. The analysis is based on empirical relations between blast parameters and non-dimensional similarity criteria. The results can be directly applied to flying vehicle (aircraft or spacecraft) blast safety analysis. Highlights: An efficient method to suppress HE effects onboard a flying vehicle was invented. Corresponding protective device was developed and tested. The results of tests at normal pressure onboard are valid also at diminished one.